2021
DOI: 10.1017/s003329172100341x
|View full text |Cite
|
Sign up to set email alerts
|

Social and occupational recovery in early psychosis: a systematic review and meta-analysis of psychosocial interventions

Abstract: Background Psychosis, even in its early stages, ranks highly among the causes of disability worldwide, resulting in an increased focus on improved recovery of social and occupational functioning. This study aimed to provide an estimate of the effectiveness of psychosocial interventions for improving functioning in early psychosis. We also sought evidence of superiority between intervention approaches. Methods An electronic search was conducted using PubMed and PsycINFO to identify origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 57 publications
1
21
1
Order By: Relevance
“…The review indicates that interventions with a bio-psycho-social integrative approach combining for example psychoeducation and family or group interventions might be more effective than control conditions in reducing symptoms and improving functioning. These results are in line with recent systematic reviews focusing on RCT studies for adolescents with psychotic disorders ( 21 ) and on psychosocial interventions aiming to improve social and occupational function in the early stages of psychosis ( 69 ), which concluded that “psychosocial interventions, particularly when provided as part of a multi-component intervention model and delivered in community-based settings are associated with significant improvements in social and occupational function.” It has been suggested that CBT would be the recommendable psychosocial treatment for adults with psychotic disorders ( 11 , 70 ), but this outcome was not supported in our systematic review, which included young adults, since CBT outperformed the control treatments only in some of the outcome domains. Frawley et al ( 69 ) also reported that interventions based on CRT significantly outperformed symptom-focused CBT interventions, while the largest gains were associated with multi-component interventions.…”
Section: Discussionsupporting
confidence: 88%
“…The review indicates that interventions with a bio-psycho-social integrative approach combining for example psychoeducation and family or group interventions might be more effective than control conditions in reducing symptoms and improving functioning. These results are in line with recent systematic reviews focusing on RCT studies for adolescents with psychotic disorders ( 21 ) and on psychosocial interventions aiming to improve social and occupational function in the early stages of psychosis ( 69 ), which concluded that “psychosocial interventions, particularly when provided as part of a multi-component intervention model and delivered in community-based settings are associated with significant improvements in social and occupational function.” It has been suggested that CBT would be the recommendable psychosocial treatment for adults with psychotic disorders ( 11 , 70 ), but this outcome was not supported in our systematic review, which included young adults, since CBT outperformed the control treatments only in some of the outcome domains. Frawley et al ( 69 ) also reported that interventions based on CRT significantly outperformed symptom-focused CBT interventions, while the largest gains were associated with multi-component interventions.…”
Section: Discussionsupporting
confidence: 88%
“…Evidence-based psychosocial treatments for psychosis have strong support for improving symptoms and recovery outcomes among people with serious mental illness (SMI), including schizophrenia spectrum disorders ( Bighelli et al, 2021 ; Frawley et al, 2021 ; Turner et al, 2018 ). However, as few as 10% of people with a diagnosed SMI receive these interventions ( Dixon et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is an urgent need for treatment optimization. As modern treatment concepts more and more aim at full recovery rather than mere reduction of clinical symptoms multi-component treatment packages are being developed (6)(7)(8). Treatments that directly target key determinants of functional outcome, such as cognitive functioning, social behavioral skills, and negative symptoms, seem to be the most promising components of such approaches.…”
Section: Introduction Backgroundmentioning
confidence: 99%